Remittances Economic Growth and Investment Nexus: Evidence From Nepal - Chaudhary, Shashi Kant (NRB Economic Review, 2022)
This paper assesses the contribution of remittances on GDP and private gross fixed capital formation of Nepal by employing the ARDL bound test approach. The model incorporates the level of financial development, and the institutional quality of Nepal as regressors in addition to the macroeconomic regressors recognised by the literature. Perron’s (1997) innovation outlier model of breakpoint unit root test has been used to confirm the suitability of the variables in the ARDL bounds test approach. The findings show a positive effect of remittances on GDP while a negative effect on private gross fixed capital formation. The paper concludes that remittances do not act as a source of capital flows in the context of Nepal, rather they behave as compensatory transfers to the recipient households. To align remittances in productive activities such as self-employment, financial investment, etc., a remittance-focused policy is advised to reach out the recipients and provide them rigorous advisory and training supports.